2009
DOI: 10.1074/jbc.m805118200
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Amyloid Fibrils of a β2-Microglobulin Fragment by Laser Beam Irradiation

Abstract: To understand the mechanism by which amyloid fibrils form, we have been making real-time observations of the growth of individual fibrils, using total internal fluorescence microscopy combined with an amyloid-specific fluorescence dye, thioflavin T (ThT). At neutral pH, irradiation at 442 nm with a laser beam to excite ThT inhibited the fibril growth of ␤ 2 -microglobulin (␤2-m), a major component of amyloid fibrils deposited in patients with dialysis-related amyloidosis. Examination with a 22-residue K3 fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…The reactions in the present study require ThT, indicating that laser-excited ThT plays an important role. Given previous results with the K3 peptide of ␤ 2 -microglobulin and A␤(1-40) (23,24), the laser-dependent destruction can be explained as follows.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The reactions in the present study require ThT, indicating that laser-excited ThT plays an important role. Given previous results with the K3 peptide of ␤ 2 -microglobulin and A␤(1-40) (23,24), the laser-dependent destruction can be explained as follows.…”
Section: Discussionmentioning
confidence: 86%
“…6, A and B). Our previous studies have shown that the His residue was modified by laser-induced active oxygen (23,24). Cys, Met, Tyr, His, and Trp are susceptible to oxidation.…”
Section: Direct Observation Of Amyloid Fibrils Of Keratoepithelin Pepmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19] Studies on 2-m illustrate a basic mechanism of amyloid fibrillation. Dialysis-related amyloidosis is a common and serious complication in patients receiving hemodialysis for more than 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,15,17,39 Therefore, the direct identification of the binding behaviors of ThT with peptide strands at the molecular level would be very interesting. The large-scale STM image (Figure 2A and Figure S5A in the Supporting Information) illustrates the binding modes of the labeling molecules ThT with GNNQQNY peptides.…”
Section: ' Results and Discussionmentioning
confidence: 99%